Syncope Caused by Huge Hiatal Hernia. (15th September 2011) - Vanerio, Gabriel
Abstract : A 84-year-old white female had a brief loss of consciousness while playing bridge. A few minutes before the episode she had eaten pizza and significant amount of carbonated soft drinks. After recovery, her friends noticed that she was alert, but pale and sweating. Upon arrival at the emergency room, sitting blood pressure was 160/60 mmHg with a normal sinus rhythm. A chest X-Ray was performed, which was essential to make the diagnosis. The X-Ray showed a large retrocardiac opacity with air and liquid level compatible with a giant hiatus hernia. After a copious snack the hiatal hernia compressed the left atrium, decreasing the left cardiac output, elucidating the mechanism of the syncopal episode. In patients presenting with swallow syncope (particularly after a copious meal, validating the importance of a careful history), a chest X-Ray should be always be performed.